Malignant Peritoneal Mesothelioma Presenting with Unresolving Haemorrhagic Ascites: A Case Report - Khushboo; Bikash Kumar; Ramesh Chandra; Vinay Mishra (Medicine and Medical Research: New Perspectives Vol. 3, 2024)
Aim: We report a case of malignant peritoneal mesothelioma presenting with persistent haemorrhagic ascites. Background: Peritoneal mesothelioma being a rare tumour, is difficult to diagnose and start treatment. The most common site for mesothelioma is the pleura, which is followed by the peritoneum as the second most common site. In certain instances, synchronous pleural and peritoneal mesotheliomas are seen (around 30–45% of cases). Because mesothelioma may not always show with particular symptoms or clinical findings, diagnosis can be challenging. In addition, in the absence of previous asbestos exposure, a delay in the diagnosis takes place. Here we report a case of malignant peritoneal mesotheliomas. The diagnostic and therapeutic approaches for these rare neoplasms are discussed. Presentation of Case: We present a case of a 24-year-old male patient with complaints of pain abdomen (on and off) and abdominal distension for 15 days, with no inhalational exposure to asbestos, causing diagnostic confusion. He had a prior history of persistent haemorrhagic ascites, with no drug allergy. A diagnostic laparoscopy was done, showing multiple omental nodules. Omental biopsy along with immunohistochemistry leads to diagnosis of malignant peritoneal mesothelioma. Discussion and Conclusion: Clinical cases of peritoneal mesotheliomas are uncommon. However, peritoneal mesotheliomas should be evaluated as one of the differential diagnoses for individuals presenting with chronic abdominal pain and ascites. Diagnosis is often overlooked by radiological investigations. Thus, a thorough clinical assessment and an extensive approach are needed to diagnose and properly treat potential patients with peritoneal mesotheliomas.